(untitled) (Advancements in Homeopathic Research, 2024)
Hair loss is one of the most prevalent complaints in patients shortly after being infected with Covid-19, reported more commonly in women. The most likely cause could be either the pathogenetic aspects or psychiatric complications of Covid-19, which can lead to the appearance or aggravation of hair loss. Homoeopathy has a vital role to play in such areas; where no specific therapeutic intervention is available in modern medicine especially when the disease is stress induced. Since Homoeopathy is the only healing science that takes care of the patient as a whole; the root cause, the physical and mental state of the patient along with the disease symptoms which individualizes the patient from one another are the basis of accurate and effective homoeopathic prescription. Following the cardinal principles, significant improvement and recovery was seen in such cases with homoeopathic remedies.